"The show must be told". The verbalization of the show in the recent spanish-american narrativa - Mesa Gancedo, Daniel (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
This article proposes a hypothesis to the discussion of the transmedial paradigm in cultural studies: the relevance of the concept of "narrative of the show" to understand a certain trend in contemporary Spanish-American literature. The study is based on a corpus of about fifteen Hispanic-American works from the last two decades, considered as a sample field and not as specific "cases" of analysis. The aim is to detect how the representation of audiovisual fictions, artistic performances or video games passes into the verbal regime. The essay seeks a literary approach to the aforementioned transmedial paradigm and, for this purpose, it uses critically proven narratological categories, particularly related to the starting hypothesis, such as the showing / telling opposition. Proposing that the verbalization of the show necessarily leads to a spectacularization of the word, what is here suggested is the consideration of this type of narration as a (perhaps epochal) strategy to question - once again - realism in literature.
Keywords: Narrative; Latin America; XXIst century; show; narratology; showing / telling; transmedia; TV shows; film; art; video games